Antioxidant activity of natural compounds supported on mesoporous Silica - Guntero, Vanina A.; Ferretti, Cristian Alejandro; Mancini, Pedro M. E.; Kneeteman, María N. (My University, 2019)
The preparation of new composites and their antioxidant properties are reported in this study. Eugenol, vanillin and cinnamaldehyde were supported on silica material, through a microwave assisted process. N2 adsorption/desorption analysis, XRD, SAXS, TEM, FTIR and XPS were used to characterize these materials. The results proved that these compounds were successfully anchored into the channels of mesoporous silica and that the ordered mesoporous structure of inorganic material was well preserved. The antioxidant activities of composites were evaluated by the phosphomolybdene method and results showed that they have a marked antioxidant activity better than free antioxidants.
Keywords: natural antioxidants; natural compounds; mesoporous Silica; antioxidant